1987
DOI: 10.1071/pp9870299
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Temperature on the Contribution of Awns to Yield in Wheat

Abstract: The effect of temperature during grain set and grain growth on the contribution of awns to yield in wheat was examined in the Canberra phytotron. For eight pairs of awned and awnless near-isogenic lines, the mean advantage of the awned lines in grain dry weight per ear was greatest when plants were held at 21/16°C during grain development, less at 27/22°C and least at 15/10°C where grain weight per ear was highest. One pair, G16 (awned) and G18 (awnless), examined more closely, showed the same response wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
1
1
0
1
Order By: Relevance
“…Some studies reported that presence of awns could be either positive (Martin et al, 2003;Weyhrich et al, 1994) or negative (McKenzie, 1972) for wheat yield, depending on growing conditions (Knott, 1986;Motzo and Giunta, 2002;Maydup et al, 2010) and genotypes (Martin et al, 2003). In a study developed by Rebetzke et al (2016) with NILs, the presence of awns was associated to larger average grain size (confirming previous studies: Olugbemi and Bush, 1987;Bort et al, 1994;Weyhrich et al, 1995) though not necessarily increasing yield as grain number was reduced. Reduction in grain number was interpreted to be related to the cost of assimilates destined to awn development (Rebetzke et al, 2016).…”
Section: Introductionsupporting
confidence: 70%
“…Some studies reported that presence of awns could be either positive (Martin et al, 2003;Weyhrich et al, 1994) or negative (McKenzie, 1972) for wheat yield, depending on growing conditions (Knott, 1986;Motzo and Giunta, 2002;Maydup et al, 2010) and genotypes (Martin et al, 2003). In a study developed by Rebetzke et al (2016) with NILs, the presence of awns was associated to larger average grain size (confirming previous studies: Olugbemi and Bush, 1987;Bort et al, 1994;Weyhrich et al, 1995) though not necessarily increasing yield as grain number was reduced. Reduction in grain number was interpreted to be related to the cost of assimilates destined to awn development (Rebetzke et al, 2016).…”
Section: Introductionsupporting
confidence: 70%
“…This is consistent with earlier reports ( Mitchell et al , 2012; 2013 ) of strong negative genotypic correlations for grain size and screenings. Awned wheats are commonly reported to produce larger grain weights, as shown for multiple backgrounds ( Knott, 1986 ; Olugbemi and Bush, 1987 ; Martin et al , 1993 ; Weyhrich et al , 1994; 1995 ; Motzo and Giunta, 2002 ; ) but this is often at the expense of fewer grains ( Teich, 1982 ; Martin et al , 1993 ; Weyhrich et al , 1994; 1995 ). Here, reduced grain size in awnletted wheats was associated with a significant reduction in grain diameter ( Martin et al , 1993 ), an important determinant of grain screenings ( Sharma and Anderson, 2004 ; Mitchell et al , 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hay contradicciones en la literatura acerca de los beneficios o penalidades de las aristas sobre el rendimiento , ver citas en Mc Kenzie, 1972). En Olugbemi & Bush (1987) describieron como variaba el rendimiento en isolíneas con y sin aristas, crecidas en sitios con diferente temperatura durante el llenado de granos. Las isolíneas aristadas alcanzaron los mayores rendimientos en el ambiente con temperatura entre 16-21 °C, rendimiento menor a 27-21°C y el ambiente donde alcanzaron los menores rendimientos fue el de 10-15°C.…”
Section: Las Aristas Y Su Posible Rol Afectando La Temperatura De La unclassified